2002
DOI: 10.3171/jns.2002.97.6.1276
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for non—small cell lung carcinoma metastatic to the brain: long-term outcomes and prognostic factors influencing patient survival time and local tumor control

Abstract: Gamma knife surgery for NSCLC metastases affords effective local tumor control in approximately 84% of patients. Early detection of brain metastases, aggressive treatment of systemic disease, and a therapeutic strategy including GKS can afford patients an extended survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
97
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 31 publications
11
97
1
3
Order By: Relevance
“…7,8,[10][11][12][13][14] In contrast, >25% of patients with lung cancer develop BM. 15,16 Unfortunately, patients with BM from CRC do not survive as long as patients with BM from other histologies. 6,17,18 This probably is secondary to the burden of systemic disease in patients with metastatic CRC to the brain; concomitant extracerebral metastases have been demonstrated in 77% to 97% of patients.…”
mentioning
confidence: 99%
“…7,8,[10][11][12][13][14] In contrast, >25% of patients with lung cancer develop BM. 15,16 Unfortunately, patients with BM from CRC do not survive as long as patients with BM from other histologies. 6,17,18 This probably is secondary to the burden of systemic disease in patients with metastatic CRC to the brain; concomitant extracerebral metastases have been demonstrated in 77% to 97% of patients.…”
mentioning
confidence: 99%
“…Outcomes of brain metastases originating from non-small cell lung carcinoma have been reported by five large studies, including this study [8,10,[27][28]. Three studies reported KPS as a significant prognostic factor on multivariate analysis [8,10], while extracranial control was reported by two studies [10,28], presence of extracranial metastasis was reported by two studies (8,28) and age was reported by two studies (8).…”
Section: Discussionmentioning
confidence: 93%
“…KPS was reported as independent prognostic factor on four studies [8,21,25], extracranial disease control on two studies [6,21], lesion number by one study (current study), age on one study (current study), lesion volume on one study [21], intracranial lesion location by one study [26], and estrogen/progesterone status on one study [21]. Outcomes of brain metastases originating from non-small cell lung carcinoma have been reported by five large studies, including this study [8,10,[27][28]. Three studies reported KPS as a significant prognostic factor on multivariate analysis [8,10], while extracranial control was reported by two studies [10,28], presence of extracranial metastasis was reported by two studies (8,28) and age was reported by two studies (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations